Pengebangan prototipe direct methanl fuel cell (DMFC) dan pengaruh kandungan nafion membrane electrode assembly (MEA) - Widodo W Purwanto; S Slamet; Martin Rifki; Isye Hayatina; Tiurma Theresa; Priyo Priyanggoro; R.S. Pattyranie; Verina JWD; Siti Rochani (Jurnal Teknik Kimia Indonesia, 2008)
The purposes of this research are designing the prototype   of DMFC, consist of graphite and aluminium cell stacks and MEA with difference Nafion content. Cell stack has active area of 6.5 cm2, and single serpentine flow field. MEAs were fabricated using Nafion membrane 117 (DuPont), gas diffusion layer (GDL) carbon cloth, and commercial catalysts E-Tek, Pt/C for the cathode side and Pt-Ru/C for the anode. Catalysts loading on the anode are 3 and 4 mgPt-Ru/cm2 and on the cathode is 3 mg/cm2. Dry Nafion content of 20 %-wt and 40 %-wt were used in this experiment. MEA fabrication was done by brush coating and hot pressing. Single cell test conducted to evaluate the performance of DMFC at 70°C with 2M methanol as fuel and air as the oxidant. The results of single cell test showed that cell voltage of 600-750 mV, current density of 100 150 mW/cm2, with maximum power density of 19 mW/cm2 ware achieved. MEA with 40 wt% Nafion content showed the better performance than 20 %-wt with power density 19 mWlcm2 and 6 mW/cm2, respectively. Increasing the catalyst loading from 3 to 4 mgPt-Ru/cm2 improved the power density from 16 to 18 mW/cm2. Keywords: Direct Methanol Fuel Cell, Cel stack, MEA, Nation content. Abstrak Penelitian ini bertujuan untuk merancang sebuah prototipe DMFC dengan cell stack berbahan grafit dan aluminium serta fabrikasi MEA dengan variasi kandungan Nafion. Cell stack memiliki luas aktif 6.5 cm2 dengan flowfield bertipe single serpentine. MEA difabrikasi menggunakan membran Nafion 117 (DuPont), lapisan difusi gas carbon cloth dan katalis komersial E-Tek, Pt/C untuk katoda dan Pt-Ru/Cuntuk anoda. Kandungan katalis adalah 3 dan 4 mgPt-Ru/cm2 pada sisi anoda dan 3 mg/cm2 pada sisi katoda. Kandungan Nafion yang digunakan adalah 20 dan 40 % berat. Fabrikasi MEA dilakukan dengan metode brush coating dan hot pressing. Uji kinerja DMFC dilakukan pada suhu 70°C dengan menggunakan bahan bakar metanal 2M dan udara sebagai oksidan. Hasil uji kinerja DMFC sel tunggal didapatkan potensial sel 600-750 mv densitas arus 100-150 mW/cm serta densitas energi maksimum 19 mW/cm2.  MEA dengan kandun?an Nafion 40 % berat memiliki kinerja yang lebih baik dengan densitas energi 19 mW/cm dibandingkan dengan Nafion 20 % berat sebesar 6 mW/cm2. Kenaikan loading katalis anoda dari 3 menjadi  4 mgPt-Ru/cm2 dapat meningkatkan  densitas  energi dari  16 mW/cm2 menjadi 18 mW/cm2.Kata kunci: Direct Methanol Fuel Cell,Cel stack, MEA, kandungan Nation.